FCNC charmed-hadron decays with invisible singlet particles in light of recent data - Geng Li; Jusak Tandean (Journal of High Energy Physics, 2023)
Abstract The flavor-changing neutral current (FCNC) decays of charmed hadrons with missing energy (Ɇ) can serve as potentially promising hunting grounds for hints of new physics, as the standard-model backgrounds are very suppressed. A few of such processes have been searched for in recent experiments, specifically D 0 → Ɇ by Belle and D 0 → π 0 Ɇ and Λ c + $$ Λ_c^{+} $$ → pɆ by BESIII, resulting in upper bounds on their branching fractions. We consider them to illuminate the possible contributions of the quark transition c → uɆ with a couple of invisible spinless bosons carrying away the missing energy, assuming that they are not charge conjugates of each other and hence can have unequal masses. We find that these data are complementary in that they constrain different sets of the underlying operators and do not cover the same ranges of the bosons’ masses, but there are regions not yet accessible. From the allowed parameter space, we show that other D-meson decays, such as D → ρɆ, and the charmed-baryon ones Ξ c → (Σ, Λ)Ɇ can have sizable branching fractions and therefore may offer further probes of the new-physics interactions. We point out the importance of D 0 → γɆ which are not yet searched for but could access parts of the parameter space beyond the reach of the other modes. In addition, we look at a scenario where the invisibles are instead fermionic, namely sterile neutrinos, and a scalar leptoquark mediates c → uɆ. We discuss the implications of the aforesaid bounds for this model. The predictions we make for the various charmed-hadron decays in the different scenarios may be testable in the near future by BESIII and Belle II.